The Distinctiveness of Small Business Owners Openness, and Conscientiousness With the Influence on Financial Institution Risk Management With the Logistic Regression Analysis in the United States - Moncayo, Luis; Kasztelnik, Karina (Journal of Accounting and Finance, 2022)
No known empirical research has focused on exploring relationship between owners’ openness, and conscientiousness with the influence on financial institution risk management in the United States. These studies cover the roots of microfinance, observed trends in the microfinance industry, the factors that have caused these trends, and the financial implications that these monies have had on the recipients and the economies in which they exist. The principal objective of this research study was to investigate the distinctiveness of small business and all other behavioral microfinance. Not significant association for the distinctiveness of small business owners’ openness, and conscientiousness were identified for our variables in this research study. Our findings of this study imply an overall significant effect of openness, and conscientiousness on small business owners’ ability to secure microloans and the influence on macroeconomy along with bank risk management after controlling for age, gender, and ethnicity. The article can contribute to a better understanding of microfinance customer behaviors and the general influence on financial institution risk.